University Students' Attitudes and Perceptions on Learning English with ChatGPT - Atakuziev, Murodjon; Margana; Gultom, Aryadi Manuel (Formosa Journal of Sustainable Research, 2024)
This study examines 43 master's students' perceptions of ChatGPT in English language learning at Universitas Negeri Yogyakarta. Using a descriptive quantitative methodology, data was gathered via questionnaires and interviews. Results show positive attitudes towards ChatGPT, with most students finding it user-friendly and beneficial for reading, writing, and cultural understanding. However, they are less confident in its ability to improve listening and speaking skills. Concerns include potential plagiarism, information leakage, and accuracy of content. Despite these issues, students find ChatGPT helpful and call for more structured guidance to enhance its integration into language learning. The study underscores the need for strategies to optimize ChatGPT’s benefits while mitigating its limitations